ANALISIS KEPEMIMPINAN PENDIDIKAN TERHADAP PROBLEMATIKA ARSIP HILANG DAN KETIDAKTERATURAN DATA DI ERA DIGITAL - Salwa Qurrota A’yun; Meisya Zahro Hasna; Cinta Amalia Hediana Putri; Leny Ariska; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of educational leadership in digital archives management, particularly in addressing the issues of lost archives and disorganized data in the digital era. This research employs a qualitative approach using a literature review method. The findings reveal that digital archival management faces complex challenges, including the risk of archive loss, data disorganization and duplication, low human resource competence, weak information security systems, and suboptimal policies and standard operating procedures. In this context, educational leadership plays a strategic role in directing policies, improving digital literacy, and integrating technology-based archival systems. Strategic efforts include implementing digital archive management systems, systematic use of metadata, strengthening information security, and developing integrated policies. Therefore, educational leadership is a key factor in achieving effective, efficient, and sustainable digital archive management. Keywords: educational leadership, archives management, digital archives, information security, digital literacy